Youth mobilities, crisis, and agency in Greece: Second generation lives in liminal spaces and austere times. Issue 3 (2nd September 2018) - Michail, Domna; Christou, Anastasia
ABSTRACT: This paper explores various dimensions of "mobility" and "agency" among second-generation immigrants in Greece who have experienced the economic crisis throughout their studies at Higher Education Institutions. Following their studies in Greece, second-generation youth migrants graduated at a time when the crisis had already been leading hundreds of thousands of mostly highly skilled Greeks to emigration, resulting in a severe "brain drain" for Greece. First-generation immigrants' investment in their children's education has been vital as an integration strategy and as a means of achieving social mobility. It has also been an asset during crisis times when the prospect of re-migration seems more than a possible option setting new challenges for youth mobility on a local, global, and transnational level. Nevertheless, the vast majority of our participants manifest their will to remain in Greece and struggle for their future in the host country. Through in-depth interviews with 130 participants, all second-generation Albanian, Bulgarian, and Romanian immigrants in Greece, 30 born in the host country and the rest in the country of origin, the paper addresses youth agency in relation to geographical mobility, education, and personal development.